Analysis of Research Methods in Construction Pollution Related Research Approaches - Afrina Qistina Ahmad Halmi, Nur; Ismail, Zulhabri; Okoroh, Michael (International Journal of Engineering and Technology, 2018)
The research method is defined as containing numerous research types, explanatory and evaluative data analysis approaches. This paper, presents a review and the analyses of prior research methods implemented to address issues that revolve around construction pollutions by observing several selected peer-reviewed journal articles. As such, 28 journal articles were selected from peer review journals published since 2000 until 2018. The journal articles were retrieved from online scholarly databases. The viability of study results is closely related to the research methods employed. As a result, the outcomes of this review indicate that qualitative research methods, such as doctrinal method, semi-structured interview, personal interview, focus groups discussion, grounded theory, and case study, are the common approaches employed in research studies. Such research techniques are deemed appropriate and reliable for implementation in future researches. In addition, a majority of researchers appear to apply the qualitative method, in comparison to the quantitative approach.Â  Thus, an effective analysis method should be able to identify the pattern of research approaches employed for non-experimental studies to address construction pollution issues. Furthermore, the findings of this study are useful for future researchers who wish to probe into the subject matter of construction pollution issues.Â Â